Columns with End Restraint and Bending in Load and Resistance Factor Design - Chen, Wai-Fah; Lui, E.M. (Engineering Journal, 1985)
In this paper, the state-of-the-art design philosophies with particular emphasis on the Load and Resistance Factor Design (LRFD) format are discussed. The background and relevant development of the design methods relating to columns and beam-columns are presented. LRFD is a limit-state design method. A valid limit-state analysis and design of structures or structural members requires more understanding of structural behavior and more demand on structural analysis techniques. For example, in the AISC/LRFD Specification, a direct second-order analysis of the structure to determine the maximum design forces in the member is recommended. Furthermore, an extensive use of stability theory is employed in the development of the specification equations.